THE HARMONIZATION OF LAW ENFORCEMENT IN THE ERADICATION OF CRIMINAL ACTS OF CORRUPTION - Siti Humulhaer (UNISSULA, 2023)
The law enforcement in eradicating criminal acts of corruption must synergize with other institutions so as to create harmonization between law enforcers so as to create legal certainty and justice for all parties. This study uses qualitative research methods that use various sources such as laws and regulations, books and scientific articles which are analyzed using the literary method. The results and discussion of this study are that in terms of the direction of eradicating corruption in the future, laws and regulations regarding law enforcement officials must be harmonized in carrying out their investigative duties and functions. To find out the extent of the effectiveness of the law, the first thing that can be measured is